Efforts by Universities to Promote Sustainability Competence Over The Last Few Decades : A Systematic Literature Review - Abdulkadir Rahardjanto; H. Husamah (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study analyzes the efforts by universities to promote sustainability competence over the last few decades and it is anticipated that it will make a valuable contribution to the advancement of literacy studies about education for sustainable development (ESD). This study employed a systematic literature review (SLR) method adapted from the PRISMA model. Qualitative data collection techniques were employed, followed by thematic analysis for data interpretation. This SLR obtained several interesting findings. It was found that the theme of SC was first collected in the Scopus database in 2009, and the increasing SC-higher education occurred during and post-COVID-19 pandemic, namely from 2020 to 2023. Various efforts have been made by universities around the world to promote SC. Their focus is on strengthening SC to realize the ESD and achieve SDGs through strengthening active learning, strengthening students and teachers, and reformulating and adapting the curriculum. It was also found that the author's country of origin is still dominated by countries in the European region, namely Spain, Sweden, and England. This fact is also supported by the concern of funding sponsors from Europe in funding research and publications regarding sustainability competencies. Therefore, this theme needs to campaign widely on other continents, especially Asia, Africa, Oceania, and America because its role and position are also important for sustainability.